A new technique for lipid core plaque detection by optical coherence tomography for prevention of peri-procedural myocardial infarction: A case report. Issue 23 (June 2017) - Kim, Yongcheol; Gnanadesigan, Muthukaruppan; van Soest, Gijs; Johnson, Thomas W.
Abstract: Rationale: Percutaneous coronary intervention (PCI) provides effective revascularization of atherosclerotic coronary arteries but the invasive nature of treatment can result in complications. Patient concerns: A 53-year old man underwent coronary angiography due to chest pain with minimal ST-segment elevation in the inferior leads of the electrocardiogram. Diagnosis: We proceeded directly to coronary angiography and delineated a moderate stenosis with haziness in the mid right coronary artery (RCA). Interventions: Expert analysis of the pre-intervention OCT imaging demonstrated a large lipid core plaque (LCP), upstream of the culprit site, with minimal thrombus burden. Subsequent implantation of a bioresorbable vascular scaffold, protected with distal deployment of a filter protection device provided an excellent result with retrieval of plaque material. Post-hoc attenuation analysis confirmed the presence of large LCP. Outcomes: A post-procedural transthoracic echocardiogram confirmed good left ventricular function with no regional wall motion abnormality. An excellent clinical outcome was achieved. Lessons: Optical coherence tomography (OCT) derived attenuation analysis can provide with qualitative and quantitative detailed evaluation of the underlying plaque substrate. Our case shows OCT can provide the interventionist with qualitative and qualitative assessment of large LCP for prevention of periprocedural complications, which may improve outcome for PCI. Abstract : Supplemental Digital Content is available in the text